2003
DOI: 10.1080/00140130310001610919
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating user satisfaction into the look-and-feel of mobile phone design

Abstract: The look-and-feel of the mobile phone was investigated using a consumer survey. Seventy-eight participants evaluated the design of 50 different mobile telephones on the perceived scale of image/impression characteristics, including: luxuriousness, simplicity, attractiveness, colourfulness, texture, delicacy, harmoniousness, salience, rigidity, and overall satisfaction. Stepwise multiple linear regression analysis were used to evaluate results. The results showed that the image and impression characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 6 publications
5
59
0
2
Order By: Relevance
“…These data are then analysed using multivariate statistics in order to try and link product perceptions and overall liking to specific product characteristics. Examples can be found in many diverse areas including automotive interiors (Bonapace, 2002;Karlsson et al, 2003;Khalid and Helander, 2004), telecommunications (Hsu et al, 2000;Yun et al, 2003), cosmetics (Nagamachi, 2002), and food science (Stone and Sidel, 2004). In contrast to these experimental approaches to data collection, generative research emphasises in-depth understanding of consumer behaviour, unmet needs, and the generation of new product ideas (Leonard and Rayport, 1997;Light, 2006).…”
Section: User-centred Design: Beyond Task Performancementioning
confidence: 99%
“…These data are then analysed using multivariate statistics in order to try and link product perceptions and overall liking to specific product characteristics. Examples can be found in many diverse areas including automotive interiors (Bonapace, 2002;Karlsson et al, 2003;Khalid and Helander, 2004), telecommunications (Hsu et al, 2000;Yun et al, 2003), cosmetics (Nagamachi, 2002), and food science (Stone and Sidel, 2004). In contrast to these experimental approaches to data collection, generative research emphasises in-depth understanding of consumer behaviour, unmet needs, and the generation of new product ideas (Leonard and Rayport, 1997;Light, 2006).…”
Section: User-centred Design: Beyond Task Performancementioning
confidence: 99%
“…Majority of males and the elderly reported that they found messaging cumbersome as while composing the message they tend to press the wrong keys mainly with mobile handsets with less space between keys especially in a rapidly changing physical environment [13][14][15][16]. Thus makes the users with larger hands and thumbs to make phone calls than to send SMS as also displayed by the present study.…”
Section: Space Between Keysmentioning
confidence: 84%
“…Similarly, keypad layout was one of the usability issues in using SMS [1,3]. Their satisfaction is also critically affected by harmoniousness that is, a feeling that the components of a product are well matched in harmony [15]. In mobile handset, the arrangement of a display and its relevant buttons may affect perceived harmoniousness.…”
Section: Overall Keypad Design Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations